Optimization of foundry processes using rheological models - Ponomarenko, O. I.; Yevtushenko, S. D.; Lukianov, I. V. (Державний біотехнологічний університет, 2025)
This study explores the importance of rheological models in sand casting, focusing on their impact on process optimization, product quality, and cost reduction.
Keywords: sand casting; rheological models; molding mixtures; process optimization